ZONA TRADISIONAL WUJUD DESENTRALISASI PENGELOLAAN TAMAN NASIONAL DI INDONESIA: PEMIKIRAN KONSEPTUAL - Edi H.S Sulistyo; Sambas Basuni; Arif Satria; Aceng Hidayat (Jurnal Analisis Kebijakan Kehutanan, 2014)
The Indonesian government has realized the importance of decentralized systems of forest resource management including the management of conservation areas by issuing Government Regulation No. 28/2011 on the Management of Sanctuary Reserve and Nature Conservation Area. The regulation is aimed at providing access to local communities to utilize resources within national parks. This paper aims to: 1) analyze  result of the decentralization of the management of national parks by examining the dimensions of property rights devolved to the local community based on the government regulation No. 28/2011; 2) the proportion  of  power transferred by central government to local communities and 3)learn  the decentralization of resource use within conservation areas in India and Nepal that possibly useful for Indonesia to adopt. This study shows that  traditional use in a national parks' traditional zone can be considered as a form of decentralization.  The level of rights that can be devolved into local communities in the traditional utilization zone is the proprietory rights. Lessons that can be learned from the implementation of decentralization in India and Nepal is that the delegation of limited rights does not produce enough change in either the condition of the resource or the relationship between the government and the local community.